Analysing Waste Management and Recycling Practices for the Hotel Industry - TANSEL, Tercan; YESHENKULOVA, Gaukhar; NURMANOVA, Ulbossyn (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
The aim of this article is to investigate waste management and recycling practices in hotel industry thouth in-depth interviews with industry professionals. The procurement, kitchen and Food&Beverage managers of five international chain hotels particicipated in the in-depth interviews (in total 15 interviews). As a result of the interviews it was determined that the three elements considered in the reduction of waste were ‘expiration date’, ‘packaging’ and ‘wholesale procurement’. There are three main reasons for the food waste generation; large portions, expiration dates and the guests themself. The staudy investigates the most common waste generated in the hotels. The results of the study have shown that geographic location is an important barrier for recycling due to the lack environmentally friendly suppliers and recycling companies in some regions.